Interfaith Harmonization: A Multi-Religious Society in Purwajaya Village, West Sumatera - Azahra, Rasela (UIN Sjech M. Djamil Djambek Bukittinggi, 2024)
This research aims to describe the variation of inter-religious harmonization process in Purwajaya Village. This research uses a descriptive approach conducted in Purwajaya Village with research subjects involving the community and religious leaders. Data collection methods include observation, interviews, documentation and triangulation, while data analysis uses data reduction, data presentation and conclusion drawing. The results showed that inter-religious harmonization in Purwajaya Village is very well maintained. People live peacefully, harmoniously, solidly despite different religions. Purwajaya Village is harmonious because of the unity of Islam, Catholicism and Protestantism. These three religions unite with the diverse attitudes of the people who gather every time there is a Purwajaya event. Inter-religious harmony is realized because of the existence of an association of people of different religions. Muslim communities in Purwajaya Village respect differences in beliefs as personal rights, encourage mutual respect, interfaith harmony, and active participation of women in socio-cultural activities. Harmonious relations with non-Muslims are reflected in invitations to Purwajaya's birthday celebrations as well as the provision of worship facilities for Catholic and Protestant religions with the provision of worship facilities for Catholic and Protestant religions with an emphasis on tolerance and community comfort.